2012
DOI: 10.1152/ajpendo.00231.2011
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle myosin expression, isoform composition, and functional activities in rat corpus cavernosum altered by the streptozotocin-induced type 1 diabetes

Abstract: Zhang X, Kanika ND, Melman A, DiSanto ME. Smooth muscle myosin expression, isoform composition, and functional activities in rat corpus cavernosum altered by the streptozotocin-induced type 1 diabetes. Am J Physiol Endocrinol Metab 302: E32-E42, 2012. First published September 13, 2011; doi:10.1152/ajpendo.00231.2011.-Diabetes mellitus (DM) is a quite common chronic disease, and the prevalence of erectile dysfunction (ED) is three times higher in this large population. Although diabetes-related ED has been stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 54 publications
1
9
1
Order By: Relevance
“…On the other hand, MHC isoform expression of the vaginal muscularis was altered by estrogen status in our study, and our findings of a decrease in the %SM1 following ovariectomy (Figures 2 and 3) with no effect on N-terminal MHC isoform expression (SMA, SMB) corroborate the results obtained in studies utilizing smooth muscle from uterus [22,53], aorta [25], and bladder [23]. Alterations in smooth muscle carboxyl-terminal isoform expression have also been reported in animal models of bladder outlet obstruction [54], diabetes [55], atherosclerosis [56], and hypertension [57]. Despite reports of changes in carboxyl-terminal isoform expression in both physiological and pathological conditions, the physiological relevance of the relative expression of SM1/SM2 isoforms is unresolved [16,[26][27][28][29][30][31]58].…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, MHC isoform expression of the vaginal muscularis was altered by estrogen status in our study, and our findings of a decrease in the %SM1 following ovariectomy (Figures 2 and 3) with no effect on N-terminal MHC isoform expression (SMA, SMB) corroborate the results obtained in studies utilizing smooth muscle from uterus [22,53], aorta [25], and bladder [23]. Alterations in smooth muscle carboxyl-terminal isoform expression have also been reported in animal models of bladder outlet obstruction [54], diabetes [55], atherosclerosis [56], and hypertension [57]. Despite reports of changes in carboxyl-terminal isoform expression in both physiological and pathological conditions, the physiological relevance of the relative expression of SM1/SM2 isoforms is unresolved [16,[26][27][28][29][30][31]58].…”
Section: Discussionsupporting
confidence: 91%
“…These results suggested that CCSM cells of diabetic ED rats tend to possess the proliferative phenotype. Our proposal contradicts a recent report by Zhang et al, 24 who studied the SM myosin expression, isoform composition and functional activities in rat corpus cavernosum altered by the streptozotocin-induced Type 1 diabetes and concluded that CCSM contractility was increased and switched to a more phasic contractile phenotype in the streptozotocin-induced Type 1 diabetic rats. This discrepancy might be attributed to the use of different isoforms of genes, as well as to the investigation of the different period of phenotype as contractile and proliferative SMCs, which represent the two ends of a spectrum of SMCs with intermediate phenotypes.…”
Section: Discussioncontrasting
confidence: 99%
“…Control experiments showed that the final concentration of 1/1,000 (vol/vol) DMSO used in these studies did not significantly modify the relaxation response. As described previously (75), rat prostatic strips were mounted longitudinally in a 4-ml organ bath (Multi-Myograph Model 810MS; Danish Myo Technology, Aarhus, Denmark). The myograph was connected in line to a PowerLab 4/30 Data Acquisition System (ADInstruments, Colorado Springs, CO) and in turn to a Dual-Core processor Pentium computer for real-time monitoring of physiological force.…”
Section: Animals and Tissuesmentioning
confidence: 99%